E-cigarette use and its influencing factors among school youths: an online survey in 13 China cities - Shengyuan LIANG; Kaiwen GUO; Xiaozhao YANG (Zhongguo gonggong weisheng, 2023)
Objective To investigate the prevalence and risk factors of e-cigarette smoking among school youths in China. Methods With stratified multistage cluster sampling, we conducted an online survey among 2 405 students aged 15 years and above from 35 high schools/vocational schools/colleges or universities in 13 China cities in 4 regions with different cultural characteristics (the north region, the Yangtze River Delta, the Pearl River Delta, and Southwest region) during September 2022 – March 2023. A questionnaire on e-cigarette use and its potential associates was compiled mainly based on Global Youth Tobacco Survey (GYTS), Chinese Perceived Stress Scale (CPSS), and Adolescent Self-Rating Life Events Checklist (ASLEC). ResultsAmong all the students surveyed, 6.36% (153) reported e-cigarette use, with 4.57% (110) and 1.79% (43) reporting ever use and current use of e-cigarette. The age at first e-cigarette use for the e-cigarette smokers was 15.92 ± 2.03 years and the number of peers on site of the students′ e-cigarette smoking was 2.10 ± 1.34. The results of unconditional multivariate logistic regression analysis revealed following risk factors for e-cigarette use: being male (odds ratio [OR] = 4.81, 95% confidence interval [95%CI]: 3.24 – 7.15), with higher stress score (OR = 1.63, 95%CI: 1.15 – 2.33), falling out of love during past six months (OR = 2.82, 95%CI: 1.89 – 4.21), losing a friend during past six months (OR = 1.67, 95%CI: 1.17 – 2.38), and having more pocket money (compared to less than 800 Chinese Yuan per month: OR800 – 1500 = 1.90, 95%CI: 1.23 – 2.95; OR > 1500 = 2.22, 95%CI: 1.44 – 3.41); while, living with married parents was a protective factor against e-cigarette use (OR = 0.44, 95%CI: 0.29 – 0.67). ConclusionThe prevalence of e-cigarette use is low and mainly influenced by gender, negative life events, amount of pocket money, and family relationship currently among school youths in China.